Behavior of High Strength Reinforced Cement Concrete with Polypropylene and Steel Fibres - Hima Bindu Kotha; Rathna Chary Mudigonda; Shrisaila Haranatti Jagadish; Venkateswara Rao Lakkoju; Vijetha Dev Padma; Vladimirovich Kotov Evgeny (MATEC Web of Conferences, 2024)
The robustness, hardness, and longevity of high strength conventional concrete have long been sought after qualities. Fibre reinforced concrete (FRC) was created to address shortcomings. The purpose of fibres used is to control cracking and to enhance tensile strength, flexural strength, toughness, impact strength, and failure mode by enhancing post-cracking ductility. To study the influence of specimen size on the flexural behavior of high strength reinforced cement concrete of 60 MPa with hybrid fibres . The current work aimed to investigate the size effect of high strength, polypropylene and steel fibre reinforced RC beams under flexure loading more realistically in addition to that how specimen size affects the flexural behaviour of 60 MPa high strength hybrid fibre reinforced cement concrete. Correspondingly three cubes of size 150 mm x 150 mm x 150 mm and the cylinders of size 100 mm diameter, 200 mm height are also cast. Three RC beams of size 150 mm x 200 mm x 1000 mm (1A), 150 mm x 300 mm x 1500 mm (2A) and 150 mm x 400 mm x 2000 mm (3A) are cast. Three hybrid fibre reinforced concrete beams (HFRC) of size 150 mm x 200 mm x 1000 mm (1B), 150 mm x 300 mm x 1500 mm(2B) and 150 mm x 400 mm x 2000 mm(3B) are cast. All beams are provided with HYSD longitudinal reinforcement of 0.52% of the cross section at 0% and 1% fibres were added. Tests Such as Compressive strength test ,Split tensile strength test and Flexural strength test was conducted.